ANALYSIS OF FACTORS AFFECTING PUBLIC INTEREST IN BECOME CUSTOMERS AT KSP SURYA ABADI MANDIRI - Uswah Hasanah; Mutiah Khaira Sihotang (Proceeding International Seminar of Islamic Studies, 2023)
The purpose of this study was to determine the factors that influence people's interest in becoming customers of KSP Surya Abadi Mandiri. This research approach used is quantitative research. The sampling technique in this study used the slovin formula, so the number of samples studied was 25 respondents. The test results obtained simultaneously, the independent variables of service, location and product together can influence the dependent variable of customer interest with the acquisition of fcount 29.018 ftable 3.03 with a significance level of 0.000. The value of R square (R2) in this study was obtained at 0.806 or 80.6%. This means that the dependent variable of customer interest can be explained by the independent variables of service, location and product by 80.6% while the remaining 19.4% is explained by other variables outside the research variables used. Partially, the service variable has a positive and significant influence on customer interest with a tcount value of 4.957 ttable 2.073 with a significance level of 0.000. The location variable partially has a positive and significant influence on customer interest with the acquisition of tcount 3.168 ttable 2.073 with a significance level of 0.005. The product variable partially has no significant effect on customer interest with a tcount of 0.400 ttable of 2.073 with a significance level of 0.312.